“Knotted electrical wire with a glass tube at the top as a foreign body in a male urethra: a case report” - Arian Karimi Rouzbahani; Bahar Amiri; Ahad Fazeli; Behzad Yousefi Yeganeh (BMC Urology)
Abstract Background A large number of self-inflicted foreign bodies have been reported in the male urethra and urinary bladder. Polyembolokoilamania is a Greek derivative describing the behavioral phenomenon of inserting foreign objects into bodily orifices. Case presentation We report a 27-year-old unmarried male who presented the emergency department after inserting a knotted electrical wire with a glass tube at the top of his bladder. The patient admitted he inserted soft objects into his penis for pleasure, curiosity, feelings of emptiness, and the need for sexual excitement. A pelvic x-ray confirmed the presence of a knotted wire stump within the urinary bladder. Faced with these challenges, we tried utilizing a 7.5 F, 26-cm pediatric flexible cystoscope. Despite our best efforts, the tightness of the knot proved insurmountable. Under spinal anesthesia, a suprapubic cystotomy was performed, and the wire was untied and retrieved from the urinary bladder via the urethra. Conclusion When the urethra is too narrow for an adult cystoscope, a pediatric cystoscope can be a considerable intervention option.